2005
DOI: 10.1038/sj.bjc.6602658
|View full text |Cite
|
Sign up to set email alerts
|

Breast and other cancers in 1445 blood relatives of 75 Nordic patients with ataxia telangiectasia

Abstract: Epidemiological studies have consistently shown elevated rates of breast cancer among female blood relatives of patients with ataxia telangiectasia (AT), a rare autosomal recessive disease. A large proportion of the members of AT families are carriers of AT-causing gene mutations in ATM (Ataxia Telangiectasia Mutated), and it has been hypothesised that these otherwise healthy carriers are predisposed to breast cancer. This is an extended and enlarged follow-up study of cancer incidence in blood relatives of 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 17 publications
3
30
0
Order By: Relevance
“…This finding has been confirmed in other studies of A-T families (Athma et al, 1996;Inskip et al, 1999;Janin et al, 1999;Geoffroy-Perez et al, 2001;Olsen et al, 2001Olsen et al, , 2005Thompson et al, 2005b). The overall relative risk of breast cancer in A-T heterozygotes is estimated to be 2.23 (95% CI ¼ 1.16-4.28) compared with the general population, and 4.94 (95% CI ¼ 1.90-12.9) in those younger than age 50 years (Thompson et al, 2005b).…”
Section: Introductionsupporting
confidence: 65%
“…This finding has been confirmed in other studies of A-T families (Athma et al, 1996;Inskip et al, 1999;Janin et al, 1999;Geoffroy-Perez et al, 2001;Olsen et al, 2001Olsen et al, , 2005Thompson et al, 2005b). The overall relative risk of breast cancer in A-T heterozygotes is estimated to be 2.23 (95% CI ¼ 1.16-4.28) compared with the general population, and 4.94 (95% CI ¼ 1.90-12.9) in those younger than age 50 years (Thompson et al, 2005b).…”
Section: Introductionsupporting
confidence: 65%
“…However, there are indications that factors such as age and the specific mutation may influence breast cancer risk. Epidemiological analyses suggest that the risk of breast cancer in ATM carriers is higher in women under 50 years and may be higher in first-degree relatives of ataxia-telangiectasia cases compared to more distantly related ATM heterozygotes (Olson et al, 2005;Thompson et al, 2005b). The breast cancer risk in individuals above and below 50 years was not significantly different in the study by Renwick et al (2006) but there was limited power to investigate the age-specific risks of ATM mutations.…”
Section: Future Challengesmentioning
confidence: 90%
“…Epidemiological studies have consistently shown that female relatives of A-T patients are at an increased risk for developing breast cancer (reviewed in Hall, 2005). Interestingly, this increased risk was predominantly observed in the mothers of A-T carriers and not in siblings and offsprings (Olsen et al, 2005). Yet, not all studies confirmed the associated breast cancer risk conferred by being an ATM heterozygous mutation carrier (Vorechovsky et al, 1996;FitzGerald et al, 1997;Bay et al, 1998;Chen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%